The Application Of Principles Of Sustainable Development In Feasibility Study - Rahim, Nor Aini (Universiti Sains Malaysia, 2006)
Sustainable development is a strategy by which communities seek economic development approaches that also benefit the local environment and quality of life. It has become an important guide to many communities that have discovered that traditional approaches to planning and development are creating, rather than solving, societal and environmental problems.